PREVALENCE OF BOVINE ANAPLASMOSIS IN IRAQ - M.A. Latif, B.; R. Ali, S. (The Iraqi Journal of Veterinary Medicine, 1989)
Blood samples from 580 cattle were examined for detection of anaplasmosis. Results of thin blood smears showed an infection rate of 26.6% for the three regions of Iraq. This rate was highest for the northern region, when the rapid card agglutination (CT) method was used, similar trend was observed with a higher sensitivity as compared to the results obtained by thin blood smears. The rates of infection with CT method were 53%, 26.6% and 29.6% for the nothern, middle and southern regions respectively. Results of this study present the first record of the incidence of cattle anaplasmosis in this country..